Human Dental Pulp Stem Cells Display a Potential for Modeling Alzheimer Disease-Related Tau Modifications - Gazarian, Karlen; Ramirez-Garcia, Luis; Tapía Orozco, Luis; Luna-Muñoz, José; Pacheco-Herrero, Mar (Frontiers in Neurology, 2021)
We present here the first description of tau in human dental pulp stem cells (hDPSCs) evidenced by RT-PCR data on expression of the gene MAPT and by immunocytochemical detection of epitopes by twelve anti-tau antibodies. The tau specificity of eight of these antibodies was confirmed by their affinity to neurofibrillary tangles (NFTs) in Alzheimer’s disease (AD) postmortem brain samples. We therefore used hDPSCs and AD brain samples as a test system for determining the probability of the involvement of tau epitopes in the mechanisms converting tau into NFT in AD. Three antibodies to non-phosphorylated and seven antibodies to phosphorylated epitopes bound tau in both DPSCs and AD NFTs, thus suggesting that their function was not influenced by inducers of formation of NFTs in AD brain. In contrast, AT100 that recognizes an hyperphosphorylated epitope did not detect it in cytoplasm of DPSCs but detected in AD brain NFT demonstrating its AD-diagnostic potential. This indicated that the phosphorylation/conformational events required for the creation of this epitope does not occur in normal cytoplasm and is a part of the mechanism(s) leading to NFT in AD brain. The TG3 bound tau in cytoplasm and in mitotic chromosomes but did not find it in nuclei. Collectively, these observations characterize hDPSCs as a novel tau-harboring neuronal lineage long-term propagable in vitro cellular system for the normal conformational state of tau sites, detectable by antibodies, with their state in AD NFTs and revealing those involved in the pathological processes converting tau into NFTs in the course of AD. With this information one can model the interaction of tau with inducers and inhibitors of hyperphosphorylation toward NTF-like aggregates to search for drug candidates. Additionally, the clonogenicity of DPSCs provides the option for generation of cell lineages with CRISPR-mutagenized genes of familial AD modeling.